Study of Adult and Pediatric Spanish Patients with Cryptogenic Splenomegaly and Splenectomy - Marta Morado Arias; Jesús Villarrubia Espinosa; Isidro Vitoria Miñana; Enrique Calderón Sandubete; Víctor Quintero; Miguel Ángel Torralba-Cabeza (Diseases)
Introduction: The differential diagnosis of splenomegaly is a complex process that encompasses a wide variety of diseases. Moreover, it is not always standardized and lacks a definitive consensus on which tests should be performed and in what order. Gaucher disease (GD) and acid sphingomyelinase deficiency (ASMD) are lysosomal diseases (LD) that present with splenomegaly, the diagnosis of which requires a high index of suspicion and specific biochemical and genetic techniques. The aim of the project for the education and diagnosis of Gaucher disease and acid sphingomyelinase deficiency (PREDIGA) was to conduct educational training alongside an observational, multicenter, ambispective, cross-sectional, single-cohort study among patients having an enlarged spleen or undergone splenectomy to further assess these subjects to exclude two lysosomal diseases, namely GD and ASMD. Methods: Using dried blood spot (DBS) testing, we identified patients with abnormally low values of the enzymes glucocerebrosidase and acid sphingomyelinase, who then underwent sequencing of the GBA1 and SPMD1 genes, respectively. The study involved 34 hospitals and 52 medical specialists. Results: We identified 220 patients (208 adults and 12 children under 18 years) with cryptogenic splenomegaly or who had undergone splenectomy (12 patients) without having reached a diagnosis. The median age was 11 years (interquartile range [IQR] 3–16) in the pediatric population and 51 years (IQR 38–65) in the adult population. Lower-than-normal enzyme values were detected in 19 DBSs, confirming eight positive cases, which corresponded to six patients with GD and two with ASMD. The rest of the DBSs with low enzyme activity were not genetically confirmed (58%). We determined that lysosomal diseases accounted for 3.6% of cryptogenic splenomegaly/splenectomy cases in our setting: 2.7% were GD and 0.9% ASMD, in a ratio of 1 ASMD patient to every 3 GD patients. Lyso-GL1 values in patients with GD were elevated in all but one individual, corresponding to a child diagnosed at 4 months old. The variants detected in the GBA1 gene were consistent with the most frequent variants found in Spain. Discussion/Conclusion: The development and implementation of this protocol for the education and diagnosis of cryptogenic splenomegaly/splenectomy, even in asymptomatic patients, constitutes a comprehensive, simple, rapid, and effective screening method for the diagnosis of GD and ASMD.